A CASE STUDY OF PROSODIC PHRASAL GROUPING AND INTONATIONAL PROMINENCE IN LANGUAGE ACQUISITION - Susanto Susanto (English Review: Journal of English Education, 2016)
In language acquisition, children use prosody in their comprehension and production of utterances. In line with that, as a case study in this research, I analyze two particular aspects of prosody in a child’s language acquisition, i.e. prosodic phrasal grouping and intonational prominence. In the first aspect, I investigate whether the child uses prosodic phrases to group words together into interpretable units. In the second aspect, I analyze whether the child uses intonational prominence to focus marking prosody. The result indicates that both aspects are used by the child.Keywords: language acquisition, prosody, intonation, phonetic cues.